1995
DOI: 10.1042/bj3110239
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of C-CAM1: effects of the cytoplasmic domain on cell aggregation

Abstract: C-CAMs are epithelial cell-adhesion molecules of the immunoglobulin supergene family with sequences highly homologous to carcinoembryonic antigen (CEA). C-CAMs and their human homologues, biliary glycoproteins, are unique among the CEA-family proteins in that they have cytoplasmic domains. Furthermore, alternative splicing generates C-CAM isoforms with different cytoplasmic domains, suggesting that the cytoplasmic domains of C-CAM may play important roles in regulating the function or functions of C-CAM. By us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In the case of CEACAM1-L, its cytoplasmic domain has been shown to be phosphorylated on Ser/ Thr residues by PKC (49) and on Tyr residues in its ITIM motif by Src kinases (19,23). Attempts to disrupt cell-cell association by mutation of the Tyr residues to Phe in the ITIM motif failed to change the cell-cell adhesion phenotype (50), and the large number of Ser/Thr residues in the CEACAM1-L domain have discouraged investigators from performing further mutational analysis. Although some light was thrown on the problem when Obrink and co-workers (27,28,46) showed that the cytoplasmic domain of rat CEACAM1-S and the juxtamembrane residues of the CEACAM1-L cytoplasmic domain bound calmodulin, little was known about further downstream targets or the consequences of the PKC phosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CEACAM1-L, its cytoplasmic domain has been shown to be phosphorylated on Ser/ Thr residues by PKC (49) and on Tyr residues in its ITIM motif by Src kinases (19,23). Attempts to disrupt cell-cell association by mutation of the Tyr residues to Phe in the ITIM motif failed to change the cell-cell adhesion phenotype (50), and the large number of Ser/Thr residues in the CEACAM1-L domain have discouraged investigators from performing further mutational analysis. Although some light was thrown on the problem when Obrink and co-workers (27,28,46) showed that the cytoplasmic domain of rat CEACAM1-S and the juxtamembrane residues of the CEACAM1-L cytoplasmic domain bound calmodulin, little was known about further downstream targets or the consequences of the PKC phosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted from its cDNA sequence, C-CAM1 contains four extracellular Ig-like domains, a transmembrane domain, and a cytoplasmic domain. By site-directed mutagenesis, we have shown that the ®rst Ig-domain is essential for adhesion, whereas the second, third, and fourth Ig-domains and the cytoplasmic domain are not (Cheung et al, 1993b;Lin et al, 1995;Olsson et al, 1995). The fact that C-CAM1 has both cell-adhesion and growth-suppressive activities suggests that these two functions may be related.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that rat CEACAM1 and human CEACAM1-4L, CEACAM1-3L, CEACAM1-4S, and CEACAM1-1L transfectants adhere homophilically. 5,6,22,23,30,[43][44][45] We have examined the ability of human CEACAM1-4L, CEACAM1-4S, and CEACAM1-1S transfectants to adhere directly to immobilized recombinant proteins carrying the entire extracellular domain CEACAM1-4L/S. Our results show that, despite the higher level of CEACAM1-1S expression on CHO-CEACAM1-1S transfectants, only the CEACAM1-4L and CEACAM1-4S transfectants were able to bind significantly (30%-62% of the input cells added) to immobilized CEACAM1-4-Fc molecules ( Figure 2).…”
Section: The Human Ceacam-4l and Ceacam-4s Isoforms Both Mediate Homomentioning
confidence: 99%